Modern systems analysis and design - Hoffer, Jeffrey A.; George, Joey F.;Valacich, Joseph S. (Boston, Massachusetts : Prentice-Hall, 2011)
The methods and principles of systems development. Modern Systems Analysis and Design uses a practical, rather than technical, approach to help readers learn the methods and principles of systems development. The sixth edition has been streamlined and updated to reflect the latest trends, information, and practices in the discipline.
The systems development environment -- The origins of software -- Managing the information systems project -- Identifying and selecting systems development projects -- Initiating and planning systems development projects -- Determining system requirements -- Structuring system process requirements -- Structuring system data requirements -- Designing databases -- Designing forms and reports -- Designing interfaces and dialogues -- Designing distributed and internet systems -- System implementation -- Maintaining information systems.
Includes bibliographical references and index.
Keywords: SYSTEM ANALYSIS